Use of temporalis fascia flap in the treatment of temporomandibular joint ankylosis: A clinical audit of 5 years - Suday G Rajurkar; Rushabh Makwana; Pallavi Ranadive; Mohan D Deshpande; Anand Nikunj; Dhanashree Jadhav (Wolters Kluwer Medknow Publications, 2017)
Aim: Restoration of normal function and jaw movements in patients with temporomandibular joint (TMJ) ankylosis has been a challenge. Various techniques have been provided for its treatment; but the results have been variable. The purpose of this paper is to present an easy and versatile method for the treatment of TMJ ankylosis and to decrease postoperative complications such as reankylosis. Materials and Methods: This paper is a review of surgical outcome of interposition arthroplasty with temporalis fascia in 17 patients of unilateral TMJ ankylosis who underwent the above procedure. The review is based on the pre-, intra- and post-operative evaluation of these seventeen patients who were treated between 2008 and 2013. The follow-up time was 1-5 years. Results: Reankylosis was seen in only one of the patients; the remaining patients had satisfactory mouth openings. Conclusion: Surgical treatment of TMJ ankylosis with interposition of temporal fascia is an effective and easy procedure for prevention for reankylosis. The autogeneous nature and proximity to the joint are the main advantages of the temporal fascia flap when compared with other interpositional materials.